IMPLIKASI BENCANA TERHADAP KEHARMONISAN RUMAH TANGGA (Studi Kasus Pada Masyarakat Korban Bencana Banjir di Kelurahan Kepatihan Kecamatan Kaliwates Kabupaten Jember) - Winning Son Ashari; Muhammad Nurul Fahmi (Sekolah Tinggi Dirasat Islamiyah Imam Syafi'i Jember, 2021)
Harmony in the household is a dream and hope for every married couple who is in a marriage relationship. This harmony must have many aspects that can affect it. Among the aspects that might affect this harmony is a tragedy that has befallen. The flood disaster has hit some areas in Jember Regency and has had several impacts on the affected residents. The purpose of this research is to find and analyze things that affect household harmony in an Islamic perspective, the phenomenon of the flood disaster in Kepatihan Jember and the implications of the flood disaster on the household harmony of flood victims in Kepatihan Subdistrict, Kaliwates District, Jember Regency. This research uses a qualitative approach with a type of case study. The results of this research are (1) In a Islamic perspektive, there are several efforts that can be made to build family harmony before and after the marriage, (2) residents of Kepatihan Jember Regency have experienced floods five times and the last disaster was the most severe by the number of residents. As many as 32 families and eight houses were affected by damage, (3) this flood disaster greatly affected the husband's ability to fulfill his obligations as head of the household, but this did not have a major negative impact on the harmony of their household.